2014
DOI: 10.1039/c4ce01278j
|View full text |Cite
|
Sign up to set email alerts
|

C–H⋯H–C and C–H⋯π contacts aid transformation of dimeric to monomeric anthracene in the solid state

Abstract: C–H⋯H–C and C–H⋯π interaction assisted formation of thermodynamically stable blue emissive AP-I from kinetically stable green emissive AP-II of 1-(anthracen-9-yl)pyrene (AP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The Cambridge Structural Database (CSD) provides an excellent platform for a comprehensive study of a series of F⋅Q derivatives crystallized over around half a century. Our continued interests in devising de novo strategies to modulate crystal structure to enhance the functional properties of materials led to a comprehensive database study on F⋅Q‐based co‐crystals. In the current study, crystal structures of F⋅Q derivatives identified from CSD were critically analyzed with the aim of introducing a general classification of multicomponent D‐A crystals based on their packing modes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cambridge Structural Database (CSD) provides an excellent platform for a comprehensive study of a series of F⋅Q derivatives crystallized over around half a century. Our continued interests in devising de novo strategies to modulate crystal structure to enhance the functional properties of materials led to a comprehensive database study on F⋅Q‐based co‐crystals. In the current study, crystal structures of F⋅Q derivatives identified from CSD were critically analyzed with the aim of introducing a general classification of multicomponent D‐A crystals based on their packing modes.…”
Section: Introductionmentioning
confidence: 99%
“…Ac ombined study based on as eries of F·Q-based co-crystals to address the subtle intermoleculari nteractions that dictate the crystalline packinga nd its corresponding structure-packing-property relationship remains elusive. The Cambridge StructuralD atabase (CSD) [44] provides an excellent platform for ac omprehensive study of as eries of F·Q derivatives crystallized over aroundh alf ac entury.O ur continued interests in devising de novo strategies to modulate crystal structure to enhance the functional properties of materials [45][46][47][48][49][50][51] led to ac omprehensive database study on F·Q-based co-crystals. In the current study,c rystal structures of F·Q derivatives identified from CSD were critically analyzed with the aim of introducing ag eneral classification of multicomponent D-A crystalsb ased on their packing modes.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of interactions involving halogens in the absence of strong hydrogen bonds has been well established in the crystal engineering community (O'Hagan, 2008;Mondal et al, 2018). The evaluation of weak interactions involving halogens in the presence of strong hydrogen bonds has generated extensive interest in recent literature, particularly in the areas of isostructurality (Dey & Chopra, 2017), polymorphism (Prohens et al, 2012;Cruz Cabeza & Bernstein, 2014), cocrystals (Chattoraj et al, 2014;Mondal, Rao et al, 2017;Eccles et al, 2012), crystal structure prediction (Hulme et al, 2005), host-guest chemistry (Noa et al, 2016), nanoindentation (Mondal, Kiran et al, 2017;Rupasinghe et al, 2015) and supramolecular chemistry (Mondal, Yadav et al, 2017;Nagarajan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hirshfeld surface (HS) analyses (Figures S3–S4 in the Supporting Information) were carried out to probe the percentage of weak intermolecular interactions present in crystalline 1 – 3 . Evaluation of the packing motif of anthracene units in the crystalline state was carried out by calculating the ρ value ( ρ =(%C⋅⋅⋅H)/(%C⋅⋅⋅C); Figure , Table S4 in the Supporting Information) for crystalline derivatives 1 – 3 , as reported earlier . To estimate the accurate longitudinal and transverse slips among the nearest and non‐nearest neighbors, pitch and roll displacement analyses were carried out in crystalline 1 – 3 (Figures S5–S10 and Table S5 in the Supporting Information) .…”
Section: Resultsmentioning
confidence: 99%